2003
DOI: 10.1002/food.200390045
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic constituents and antioxidant capacities of Crataegus monogyna (Hawthorn) callus extracts

Abstract: Crataegus (Hawthorn) has long been used as a folk medicine and is widely utilized in pharmaceutical preparations mainly because of its neuro- and cardiosedative actions and its low toxicity. The pharmacological effects of Crataegus have mainly been attributed to the polyphenolic contents. In this study, the production of polyphenols by ten-year-old Crataegus monogyna calli was studied in relation to growth variation and antioxidant capacity within a subculture period. Assays based on the Trolox equivalent anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 36 publications
8
79
0
2
Order By: Relevance
“…They found that the scavenging activities of the cell suspension extracts were similar to those of the flowers. Furthermore, some reports studied the antioxidant actions of Crataegus monogyna callus cultures and showed that a high TEAC values were observed when the culture medium contained 2.0 mg/L 2,4-D and 0.5 mg/L KIN, these values were strongly influenced by the total flavonoids content (Bahorun et al 1994(Bahorun et al , 2003. In addition, Bahri-Sahloul et al showed a high DPPH radical scavenging effect in Salvia officinalis shoot cultures grown on MS medium containing a high ratio of BAP over IAA which was comparable to that of collected plants.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the scavenging activities of the cell suspension extracts were similar to those of the flowers. Furthermore, some reports studied the antioxidant actions of Crataegus monogyna callus cultures and showed that a high TEAC values were observed when the culture medium contained 2.0 mg/L 2,4-D and 0.5 mg/L KIN, these values were strongly influenced by the total flavonoids content (Bahorun et al 1994(Bahorun et al , 2003. In addition, Bahri-Sahloul et al showed a high DPPH radical scavenging effect in Salvia officinalis shoot cultures grown on MS medium containing a high ratio of BAP over IAA which was comparable to that of collected plants.…”
Section: Discussionmentioning
confidence: 99%
“…The same procedure was repeated with all standard gallic acid solutions (10-200 µg/ml).The amount of total polyphenols in different extracts were expressed as µg of gallic acid equivalent (GAE)/ mg extract. Flavonoids were quantified using aluminum chloride reagent (AlCl3) method described by [10] . The flavonoids content was expressed as quercetin equivalents (QE).…”
Section: Determination Of Total Phenolic and Flavonoids Contentsmentioning
confidence: 99%
“…The main biologically active substances detected in the medicinal vegetal raw material of monogynous hawthorn are flavonoids and their glycosides: hyperoside (quercetin-3-galactoside), quercetin, vitexin, vitexin-O-rhamnoside, isovitexin-O-rhamnoside, acetylvitexin-O-rhamnoside, rutin, quercitrin (quercetin-3-rhamnoside), orientin, kaempferol, spireoside, saponaretin, oligomeric procyanidins, catechins, and phenolic acids (chlorogenic acid, caffeic acid, triterpene saponins, etc.) (3,4).…”
Section: Introductionmentioning
confidence: 99%